Comparative Life Cycle Assessment of Two Different Models of a Home Appliance. Issue 6 (2nd November 2021) - Shaukat, M. Mobeen; Masood, Hammad; Merah, Necar; Al-Badour, Fadi A.; Qadeer, Abdul; Afzal, Soban
ABSTRACT: This study presents a comparative life-cycle assessment of two juicers, of same power rating and capacity, produced by two different manufacturers. First juicer was produced in Slovenia and the second juicer was produced in China. Life-cycle inventory for each juicer was compiled by considering all the stages of life cycle, including manufacturing, transportation, usage and end-of-life. Simapro software was used for modelling life-cycle inventory and ReCiPe method was used for impact assessment. Life-cycle assessment revealed that despite having the same power rating and capacity, two juicers have significantly different environmental impacts. Juicer produced in Slovenia consumes 50% less power and on average has 20% less environmental impacts. Compact design, efficient motor and frugal use of materials contributed to this superior environmental performance.